Seeing data differently: Developing a local instructional theory for culturally relevant statistical literacy in Indonesian teacher education - Utari, Rahma Siska; Putri, Ratu Ilma Indra; Zulkardi; Hapizah (Journal on Mathematics Education, 2025)
Statistical literacy has emerged as a central competence in mathematics education, particularly for prospective teachers who must be able to interpret, analyze, and critically evaluate data in a world increasingly shaped by information and statistics. However, previous research shows that many prospective teachers continue to struggle with developing statistical literacy, especially in connecting abstract concepts to meaningful contexts. This gap highlights the need for instructional designs that not only strengthen statistical reasoning but also draw on culturally embedded practices to enhance relevance and engagement. Addressing this challenge, the present study develops a Local Instructional Theory (LIT) that supports prospective teachers’ statistical literacy through the integration of local cultural contexts in South Sumatra, designed within the framework of Realistic Mathematics Education (RME) as adapted in Indonesia, namely Pendidikan Matematika Realistik Indonesia (PMRI). Employing a design research methodology, the study was conducted in three phases: a preliminary investigation, a design experiment (pilot and teaching experiment), and a retrospective analysis. The resulting LIT was structured around three context-based learning trajectories, each targeting a key dimension of statistical literacy: data visualization, data interpretation, and critical evaluation. Instructional activities were grounded in authentic cultural contexts—such as Pempek demand during Ramadan, the Bekarang Iwak fishing tradition, and coffee productivity in Pagar Alam—which were used to bridge statistical concepts with learners lived experiences. Findings from the teaching experiments indicate that prospective teachers demonstrated notable shifts from procedural to conceptual reasoning and from descriptive analysis to reflective critique. Participants also showed improved ability to select appropriate graphical representations, interpret contextual data, and critically assess the credibility and sufficiency of statistical information. These outcomes underscore the potential of culturally relevant instructional design to foster holistic statistical literacy. The study contributes both theoretically and practically by offering a validated model for integrating cultural contexts into mathematics education, thereby enriching prospective teachers’ curriculum and providing a replicable approach for diverse educational settings.